Implementation of Halal Products on Moeslem Traveler’s Awareness - Asri Pebrianti; Muhammad Bilgary Utama; Terry Oktriviani (Universitas Muhammadiyah Mataram, 2018)
This research illustrates how the risk scheme of consuming non-halal products for health is not onlyaboutdisadvantageto consumer health but also their economics in the the future. Halal product consumption for mankind has a good reason in terms of health and economic aspects that will be generated. This writing aims to examine the behaviormoeslemtraveler in consuming halal products, the behavior in the review is the awareness and consistency in consuming the halal products.The arguments are delivered with descriptive qualitative method. Data collecting method used literature studies from Islamic rule literature, previous research findings, and related text books. Studies of related literature that became mainreference is the halal and haram restrictions in Islam (the basic principle of consuming that has been established halal and prohibited by Allah Azza wa Jalla (absolute). Some of products allowed to be consumed and exploited until there is a special ban, as well as prohibited because obviously the ugliness of the substance and prohibited because it deals with the violation of God's right to Azza wa Jalla as it is obtained from an incorrect path), the ethics of consumption in the Islamic perspective (consuming as allowed and advocated by Al-Quran, Al-hadith and As-Sunnah). Important findingsof previous studies that have proven the negative effects of consuming non-halal products in health and financial terms. The results of this study indicate that there are benefits to get when consuming halal products, ranging from long-term health and financially in the future.Moeslem traveler could be guided with the compact information to obey halal-haram rules.